A Survey of Health Promotion at International Schools - Curless, M.; Burns, Sharyn (Wiley-Blackwell Publishing Inc, 2003)
This study investigated health promotion efforts at international schools serving the education needs of expatriate communities abroad. Factors supporting the implementation of whole-school approaches to health promotion also were examined. Self-completed questionnaires were distributed by a combination of electronic and conventional mail. International school staff in 93 countries (n = 205) completed an adapted version of an instrument used for evaluating the Western Australian School Health Project (WASHP). This survey demonstrated usefulness of the WASHP instrument cross-culturally in a variety of school settings. The level of whole-school approaches to health promotion in the participating international schools varied but tended to be low. Demographic characteristics of schools were not associated with differences in the level of health promotion, with the exception school size. School organizational factors support implementation of health promotion programs.